2006
DOI: 10.1073/pnas.0602138103
|View full text |Cite
|
Sign up to set email alerts
|

Genetic adaptation by Pseudomonas aeruginosa to the airways of cystic fibrosis patients

Abstract: In many human infections, hosts and pathogens coexist for years or decades. Important examples include HIV, herpes viruses, tuberculosis, leprosy, and malaria. With the exception of intensively studied viral infections such as HIV͞AIDs, little is known about the extent to which the clonal expansion that occurs during long-term infection by pathogens involves important genetic adaptations. We report here a detailed, whole-genome analysis of one such infection, that of a cystic fibrosis (CF) patient by the oppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

80
1,569
9
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,248 publications
(1,665 citation statements)
references
References 41 publications
80
1,569
9
7
Order By: Relevance
“…This suggests that QS may play an important role for P. aeruginosa competition against other bacterial species. For example, the proportion of lasR mutants typically increases during chronic polymicrobial CF infections (Ghoul et al., 2015; Marvig et al., 2014; Smith et al., 2006) and this could be potentially partly explained with QS‐mediated competitive interactions with other bacteria (Harrison, Paul, Massey, & Buckling, 2008). There are several mutually nonexclusive explanations for reduced P. aeruginosa growth in the presence of competitors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that QS may play an important role for P. aeruginosa competition against other bacterial species. For example, the proportion of lasR mutants typically increases during chronic polymicrobial CF infections (Ghoul et al., 2015; Marvig et al., 2014; Smith et al., 2006) and this could be potentially partly explained with QS‐mediated competitive interactions with other bacteria (Harrison, Paul, Massey, & Buckling, 2008). There are several mutually nonexclusive explanations for reduced P. aeruginosa growth in the presence of competitors.…”
Section: Discussionmentioning
confidence: 99%
“…Competition could thus enhance the phage efficacy when treating acute CF and burn infections that are commonly co‐infected by QS signalling P. aeruginosa , S. aureus and S. maltophilia (Harrison, 2007; Turner et al., 2014). However, in contrary, P. aeruginosa resistance evolution to phages could be a more severe problem in chronic polymicrobial CF infections that are often dominated by P. aeruginosa mutants that have lost QS signalling ability during the long‐term adaptation (Andersen et al., 2015; Marvig et al., 2014; Smith et al., 2006). Interestingly, we found that higher levels of lasR strain resistance evolution were correlated with the higher rate of phage infectivity evolution, which could open up avenues for pre‐adapting phages to be more infective before clinical phage therapy treatments (Betts et al., 2013; Friman et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chez 14 d'entre eux, dont le premier à avoir été infecté, on a pu, pendant 16 ans, prélever et conserver 112 isolats séquencés récemment, l'ensemble des séquences obtenues couvrant le temps de l'évolution. On a identifié 492 SNP (single nucleotide polymorphism), soit environ deux par an, taux déjà décrit chez certains pathogènes au cours d'infections prolongées [3]. La construction d'un arbre phylogénétique suggérait un réseau de transmission entre patients et permettait de reconstruire la structure du dernier ancêtre commun.…”
Section: Epidémie De Burkholderia Dolosa : Opportunité D'analyse D'évunclassified
“…Quelle est la base génétique de l'évasion immunitaire, de la résistance aux antibiotiques ? Cette question, soulevée depuis des années, a été explorée en laboratoire, soit dans des expériences d'évolution expérimentale utilisant des souches microbiennes définies que l'on repique pendant de nombreuses généra-tions dans des milieux liquides contrôlés [1,2], soit par l'étude de souches isolées au cours de processus pathologiques [3]. Ces travaux ont, cependant, été longtemps limités par les conditions techniques, essentiellement la difficulté à obtenir un nombre suffisant de séquences de génomes bactériens pour des résultats statistiquement valables.…”
unclassified